2017
DOI: 10.3945/jn.116.244749
|View full text |Cite
|
Sign up to set email alerts
|

Meal Frequency and Timing Are Associated with Changes in Body Mass Index in Adventist Health Study 2

Abstract: Scientific evidence for the optimal number, timing, and size of meals is lacking. We investigated the relation between meal frequency and timing and changes in body mass index (BMI) in the Adventist Health Study 2 (AHS-2), a relatively healthy North American cohort. The analysis used data from 50,660 adult members aged ≥30 y of Seventh-day Adventist churches in the United States and Canada (mean ± SD follow-up: 7.42 ± 1.23 y). The number of meals per day, length of overnight fast, consumption of breakfast, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
165
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(212 citation statements)
references
References 57 publications
(56 reference statements)
10
165
2
9
Order By: Relevance
“…Similarly, Kim et al (18) found that Korean adults with an EF ≥ 5 daily eating episodes compared with <3 episodes had a lower BMI, WC and body fat percentage. However, the literature still presents contradictory results for the ideal number of daily eating episodes and their benefits in nutritional status (22)(23) , providing evidence for the necessity for further studies relating to these variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Kim et al (18) found that Korean adults with an EF ≥ 5 daily eating episodes compared with <3 episodes had a lower BMI, WC and body fat percentage. However, the literature still presents contradictory results for the ideal number of daily eating episodes and their benefits in nutritional status (22)(23) , providing evidence for the necessity for further studies relating to these variables.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to diet quality, inverse associations between the number of eating episodes and anthropometric variables were identified (10,17,18) . Studies show better control of body weight and healthy maintenance of biological markers when eating episodes are lower in energy intake and more frequent (19)(20)(21) , but the results are still inconsistent because of variations in methodological factors, especially for the optimal number of meals for anthropometric benefits (22,23) . It is known that negative anthropometric changes in BC patients are already commonly observed during CT (6,24) and are negatively related to the prognosis of the disease (25,26) .…”
mentioning
confidence: 99%
“…Night Eating Syndrome, an eating disorder that involves eating 25% or more of one's daily calories after the evening meal, was associated with increased risk of obesity and changes in the timing and amplitude of metabolic hormones such as glucose, insulin, ghrelin, and leptin in adults [14,46,47]. Finally, an association between late meal timing and weight gain or obesity has been observed in observational studies among adults [48][49][50][51][52][53] and children [54][55][56]. In addition, late meal timing has been shown to affect weight loss outcomes in obesity treatment interventions [57][58][59].…”
Section: Introductionmentioning
confidence: 98%
“…In a review of 10 papers on the role of meal frequencies in weight management by healthy adults aged 20-70 Palmer et al did not show any significant dependence on weight loss or maintenance [21]. On the other hand, Kahleova et al analysing data from 50,660 adult members aged ≥30 y Seventh-day Adventist churches in the United States and Canada reports relative increase in BMI during a year in subjects who ate 3 meals/d compared with those who ate 1 or 2 meals/d [12]. It is worth to mention that such strategy worked for those who ate breakfast and lunch 5-6 h apart, consumed no snacks and made the overnight fast last 18-19 h. In studies performed by O'Connor et al in a group of 1,092 adults with a normal body weight, eating snacks between meals did not result in weight gain as well [20].…”
Section: Discussionmentioning
confidence: 96%